Projeto, construção e análise de eficiência térmica de um sistema de aquecimento solar de água de baixo custo - Gomes, Marcio Rodrigues (2014)
We studied the feasibility of using a system of Solar Water Heating (SAS) with low cost, for three configurations. In configurations I and II have the collector grid absorber composed of six PVC tubes placed in parallel on the tile cement. In configuration II, the PVC tubes were transparent cover made of plastic bottles. Configuration III uses a collector composed of 12 black HDPE pipes, supported on four cement tiles 2.44 m x 0.50 m, two by two overlapping and interspersed with a filling of glass wool, comprising an area exposed to the global radiation incident of 2.44 m2, with the top two tiles painted matte black. In this configuration, the HDPE pipes replace conventional PVC pipes painted black. The total cost of SAS for configuration III, the most economical, was around $ 150.00. For the configurations tested the system of operation was thermosyphon collector. The study showed that the proposed systems have good thermal efficiency, are easy to install and handle and have low cost compared to conventional.